1990
DOI: 10.1007/bf02549802
|View full text |Cite
|
Sign up to set email alerts
|

Serum selenium levels in healthy adults and its changes in chronic renal failure

Abstract: In this study the serum selenium levels of 500 healthy Greeks and 225 patients with chronic renal failure (CRF) were measured using Watkinson's method. The patients were treated either conservatively or by peritoneal dialysis or haemodialysis. We found that the levels were in an intermediate position compared to those of other Europeans. Selenium levels were also found to increase significantly with age. No difference was detected between male and female patients. A statistically significant drop was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
4

Year Published

1998
1998
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 8 publications
0
7
1
4
Order By: Relevance
“…Serum Se concentrations between 0.51 and 1.79 mmolaL have been reported for European populations (for example, Kostakopoulos et al, 1990;Ringstad et al, 1991). In the 1970s the serum Se concentrations in the Finnish population ranged from 0.63±0.76 mmolaL (Alfthan, 1988;Knekt et al, 1990) being among the lowest ones in Europe.…”
Section: Discussionmentioning
confidence: 96%
“…Serum Se concentrations between 0.51 and 1.79 mmolaL have been reported for European populations (for example, Kostakopoulos et al, 1990;Ringstad et al, 1991). In the 1970s the serum Se concentrations in the Finnish population ranged from 0.63±0.76 mmolaL (Alfthan, 1988;Knekt et al, 1990) being among the lowest ones in Europe.…”
Section: Discussionmentioning
confidence: 96%
“…As far as we know, there are limited studies determining serum selenium in population-based Greek cohorts. Moreover, those studies have either focused on certain population groups [8,9] or have had a low number of participants [7,15,16]. In addition, inadequate data about different factors such as anthropometric parameters and dietary habits as well as biochemical confounders that may influence the selenium status have been presented.…”
Section: Discussionmentioning
confidence: 99%
“…Of those elements, selenium (Se) acts as a major antioxidant in the form of selenoproteins to mitigate the cytotoxic effects of reactive oxygen species [3][4]. A number of studies have been reported on selenium level [5][6][7][8][9], food source [10][11][12][13], racial differences [14], deficiency [15][16][17], and toxicity [18]. Se concentration in the biological fluids varies considerably inside the global population, and normal ranges for typical populations are different [19].…”
Section: Introductionmentioning
confidence: 99%